Antifungal activity of lactic acid bacteria strains isolated from natural honey against Pathogenic Candida species - Bulgasem B.Y.; Lani M.N.; Hassan Z.; Wan Yusoff W.M.; Fnaish S.G. (Korean Society of Mycology, 2024)
Indexed by WOS/ Scopus